Levi Peirce, The Consolidation and Revision of the Statutes of the State, of a General Nature 185 (1852) - (:unkn) unknown (My University, 1852)
When gunpowder is shipped on board of a steamboat, which shall at all times be stowed away at as great a distance as possible from the furnace, a written notification of the fact shall be placed in three conspicuous parts of the boat; and in the event of such notification not being so exhibited , then for any loss of property, or life, for which the powder shall be deemed the cause, the owner shall be liable to the shipper for the full amount of said loss or damage; and the captain, in the event of loss of life being the result of such accident, shall be adjudged guilty of manslaughter.§ 6. Any person or persons who shall ship or put on board, or cause to be shipped or put on board of any steamboat, within this State, any gunpowder, without giving notice thereof a the time of making the shipment to the master clerk of said boat, shall be liable to a penalty of two hundred dollars, which may be sued for and recovered before any court of competent jurisdiction by the owner, captain or clerk of said boat, for his or her own use and benefit
Keywords: GUNPOWDER - TRANSPORTATION